Customer Journey Model for Pesticide-Free Vegetables and Longan from the Baan Pa-Hget-Tee Agricultural Group in Nong Phueng Subdistrict, Saraphi District, Chiang Mai Province, from the Farmers’ Perspective - Anunchaitawat, Veerapun; Teeyabun, Nutchari; Linruesee, Tanyarut; Jensomboon, Sanruethai; Tananchai, Tipwon; jiranantharaporn, Ravipreeya; Chaimoon, Walai; Suyarat, Sangla; Punsuwan, Worawarun; Sutar, Somsak; Yothaitiang, Wasana; Puanya, Wanida; et al. (Research and Development Journal, Loei Rajabhat University, 2025)
This research article aims to study and develop a customer journey model for pesticide-free vegetables and longan from the Baan Pa-Hget-Tee agricultural group in Nong Phueng Subdistrict, Saraphi District, Chiang Mai Province, from the Farmers’ Perspective. The study adopts a participatory action research approach, with a target population of 20 farmers residing in Baan Pa-Hget-Tee. Data were collected through participatory workshops, during which structured questions were posed to the participants. Content analysis was employed for data interpretation. The findings reveal that the customer journey consists of five key stages: 1) Awareness - consumers learn about the products through local stores, Facebook, and word-of-mouth recommendations; 2) Consideration - they seek additional information by reading reviews or consulting friends; 3) Purchase - transactions occur through convenient channels, including physical stores or farms, with bank transfers or QR code scanning payments; 4) Repeat Purchase - customers repurchase when they perceive good quality and value, often ordering via Facebook with home delivery services; 5) Advocacy - satisfied customers share their experiences by posting photos on Facebook and LINE, fostering long-term brand relationships.